When the Killing's Done - Torben C. Rick (Ethnobiology Letters, 2012)
Review of When the Killing's Done. T. Coreghessan Boyle. 2011. Viking Press, New York, NY. Pp. 384. ISBN10: 0143120395. ISBN13: 978‐0143120391